2019
DOI: 10.1186/s12910-019-0393-7
|View full text |Cite
|
Sign up to set email alerts
|

Parental decision-making following a prenatal diagnosis that is lethal, life-limiting, or has long term implications for the future child and family: a meta-synthesis of qualitative literature

Abstract: Background Information on the factors influencing parents’ decision-making process following a lethal, life-limiting or severely debilitating prenatal diagnosis remains deficient. A comprehensive systematic review and meta-synthesis was conducted to explore the influencing factors for parents considering termination or continuation of pregnancy following identification of lethal, life-limiting or severely debilitating fetal abnormalities. Methods Electronic searches of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 64 publications
2
43
1
2
Order By: Relevance
“…When interviewed about the barriers and challenges to keeping a cohesive and effective palliative care team together, the medical director of the Perinatal/Pediatric Hospice Program at The Elizabeth Hospice and a family practice in San Diego, Dr. George Delgado, said the “challenges include emotional stress, compassion fatigue, ethical dilemmas, and cost-cutting across healthcare.” From his experience most of the conflicts are ethical, extending from contrasting societal philosophical axioms influencing healthcare, which can leave professionals in an ideological betwixt and between in the delivery of care. Ethical dilemmas not only surround the termination of a live fetus but also accompany the initiation and continuation of life-sustaining treatments that can be perceived as a prolongation of suffering and an exercise in futility for an infant bound to die ( 24 , 26 , 27 ). Both options are indicated as palliative options on the spectrum of services for those diagnosed with life-limiting fetal malformations by the American College of Obstetrics and Gynecology ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…When interviewed about the barriers and challenges to keeping a cohesive and effective palliative care team together, the medical director of the Perinatal/Pediatric Hospice Program at The Elizabeth Hospice and a family practice in San Diego, Dr. George Delgado, said the “challenges include emotional stress, compassion fatigue, ethical dilemmas, and cost-cutting across healthcare.” From his experience most of the conflicts are ethical, extending from contrasting societal philosophical axioms influencing healthcare, which can leave professionals in an ideological betwixt and between in the delivery of care. Ethical dilemmas not only surround the termination of a live fetus but also accompany the initiation and continuation of life-sustaining treatments that can be perceived as a prolongation of suffering and an exercise in futility for an infant bound to die ( 24 , 26 , 27 ). Both options are indicated as palliative options on the spectrum of services for those diagnosed with life-limiting fetal malformations by the American College of Obstetrics and Gynecology ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include maternal age and medical history, religious beliefs, cultural values, severity of anomalies, expected prognosis, gestation at diagnosis, and socioeconomic status (25)(26)(27)(28). Additionally, many families consider the worth of their baby, potential quality of life, and personal ethics in the context of the known information (29)(30)(31). Several studies have shown the impact of religion on decisions for pregnancy continuation and decisions regarding care after delivery (32,33).…”
Section: Parental Decision-making Experience With a Prenatally Identimentioning
confidence: 99%
“…For example, some families will want specific spiritual care or ceremonies after birth to honor their faith. But there are also some universal themes (22). Janvier et al found that among families with children who lived with Trisomy 13 or 18, there were "common hopes to bring their child home, give their child a good life, and be together/a family" (23).…”
Section: Final Arrangementsmentioning
confidence: 99%